Hypoxic regulation of angiotensin‐converting enzyme 2 and Mas receptor in human CD34+ cells - Joshi, Shrinidh; Wollenzien, Hannah; Leclerc, Estelle; Jarajapu, Yagna PR (Journal of cellular physiology, 2019)
CD34+ hematopoietic stem/progenitor cells (HSPCs) are vasculogenic and hypoxia is a strong stimulus for the vasoreparative functions of these cells. Angiotensin‐converting enzyme 2 (ACE2)/angiotensin‐(1–7)/Mas receptor (MasR) pathway stimulates vasoprotective functions of CD34+ cells. This study tested if ACE2 and MasR are involved in the hypoxic stimulation of CD34+ cells. Cells were isolated from circulating mononuclear cells derived from healthy subjects (n = 46) and were exposed to normoxia (20% O2) or hypoxia (1% O2). Luciferase reporter assays were carried out in cells transduced with lentivirus carrying ACE2‐ or MasR‐ or a scramble‐3′‐untranslated region gene with a firefly luciferase reporter. Expressions or activities of ACE, angiotensin receptor Type 1 (AT1R), ACE2, and MasR were determined. In vitro observations were verified in HSPCs derived from mice undergoing hindlimb ischemia (HLI). In vitro exposure to hypoxia‐increased proliferation and migration of CD34+ cells in basal conditions or in response to vascular endothelial growth factor (VEGF) or stromal‐derived factor 1α (SDF) compared with normoxia. Expression of ACE2 or MasR was increased relative to normoxia while ACE or AT1R expressions were unaltered. Luciferase activity was increased by hypoxia in cells transfected with the luciferase reporter plasmids coding for the ACE2‐ or MasR promoters relatively to the control. The effects of hypoxia were mimicked by VEGF or SDF under normoxia. Hypoxia‐induced ADAM17‐dependent shedding of functional ACE2 fragments. In mice undergoing HLI, increased expression/activity of ACE2 and MasR were observed in the circulating HSPCs. This study provides compelling evidence for the hypoxic upregulation of ACE2 and MasR in CD34+ cells, which likely contributes to vascular repair. Bone marrow–derived progenitor cells are recruited to the areas of hypoxia and stimulate vascular regeneration. Exposure to hypoxia upregulates the expression of angiotensin‐converting enzyme 2 (ACE2) and Mas receptor, and ACE2 shedding in progenitor cells. Activation of Mas by angiotensin‐(1–7), a metabolite of ACE2, stimulates vasoreparative functions in progenitor cells and vascular endothelium.